2015
DOI: 10.1007/s00256-015-2277-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of lumbar epidural steroid injections using particulate vs. non-particulate steroid: an intra-individual comparative study

Abstract: The relative satisfaction with ESI_TRIAM was significantly better than that with ESI_DEXA in the same patient, and the injection-free interval after ESI_TRIAM was significantly longer than that after ESI_DEXA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Kim et al [43] examined dexamethasone and triamcinolone for lumbar ESI performed via 3 different approaches: ILESI, TFESI, and caudal ESI. The intraindividual comparison study included 162 patients with lumbar radiculopathy secondary to stenosis or disk herniation.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [43] examined dexamethasone and triamcinolone for lumbar ESI performed via 3 different approaches: ILESI, TFESI, and caudal ESI. The intraindividual comparison study included 162 patients with lumbar radiculopathy secondary to stenosis or disk herniation.…”
Section: Resultsmentioning
confidence: 99%
“…In lumbar transforaminal ESI, a nonparticulate steroid should be used for the initial injection, but there are situations in which particulate steroids could be used (55). Although early studies suggested that particulate steroids were superior to nonparticulate steroids in the duration of pain relief, recent studies suggest inconsistent results regarding a longer duration of pain relief for particulate steroids (56)(57)(58).…”
Section: Particulate Steroid Injectionmentioning
confidence: 99%
“…A prospective study from 2010 randomized 106 patients to receive DSP or TA before lumbar transforaminal ESI and concluded that TA was more effective than DSP in treating lumbar radiculopathy when assessed using the visual analog score but was statistically similar to DSP using the McGill Pain Questionnaire or the Oswestry Disability Index [87]. A retrospective study involving 139 lumbar ESIs (interlaminar, transforaminal, or caudal) included patients who received TA initially and DSP subsequently [88]. On the basis of telephone interviews 6 months after DSP injection, the study reported that patients were significantly more satisfied with TA injections compared with DSP injections.…”
Section: Efficacy Of Particulate Versus Nonparticulate Corticosteroidsmentioning
confidence: 99%